Accountability in Village Fund Management: A Qualitative Study of Transparency, Responsibility, Control, and Responsiveness in Tilango District, Gorontalo Regency - Dauhi, Kartin; Tohopi, Rustam; Tui, Fenti Prihatini; H. Badjuka, Alexander (Yayasan Abdurrauf Cendekia Nusantara, 2025)
This study examines the implementation of accountability in the management of village funds in Tilango District, Gorontalo Regency, Indonesia. The research adopts a qualitative descriptive approach within the constructivist paradigm to understand how local actors interpret and apply accountability principles in daily administrative practice. Data were collected through interviews, observations, and document analysis from village officials, community representatives, and government facilitators. The findings reveal that accountability mechanisms have been implemented but remain procedural and fragmented across five dimensions: transparency, responsibility, control, answerability, and responsiveness. Transparency is limited to formal disclosure, while responsibility is constrained by low administrative capacity. Control mechanisms are reactive rather than preventive, and accountability reports are often treated as bureaucratic requirements rather than reflective evaluations. Responsiveness to community aspirations is inconsistent, with limited follow-up on participatory decisions. These findings confirm that accountability in Tilango District demonstrates administrative adequacy but low substantive quality, aligning more with compliance than with participatory and performance-based governance. Theoretically, the study expands Aman et al.’s (2013) accountability framework within the context of Good Governance and New Public Management (NPM). Practically, it recommends capacity building, stronger preventive monitoring, and greater community engagement to improve financial transparency and institutional trust.